2022
DOI: 10.3390/ijms23020706
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 Activity Is Critical for the Outcome of Ischemic Stroke

Abstract: Ischemic disorders are the leading cause of death worldwide. The extracellular signal-regulated kinases 1 and 2 (ERK1/2) are thought to affect the outcome of ischemic stroke. However, it is under debate whether activation or inhibition of ERK1/2 is beneficial. In this study, we report that the ubiquitous overexpression of wild-type ERK2 in mice (ERK2wt) is detrimental after transient occlusion of the middle cerebral artery (tMCAO), as it led to a massive increase in infarct volume and neurological deficits by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…This activation process transfers extracellular signals through the cell membrane and cytoplasm to the nucleus to regulate the cell cycle and the physiological and pathological processes of cells [ 35 ]. Studies have shown that the ERK pathway is involved in the regulation of tight junction protein expression and is closely related to blood-brain barrier permeability [ 36 ]. ERK showed continuous overactivation during brain trauma, and its expression duration was significantly prolonged [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This activation process transfers extracellular signals through the cell membrane and cytoplasm to the nucleus to regulate the cell cycle and the physiological and pathological processes of cells [ 35 ]. Studies have shown that the ERK pathway is involved in the regulation of tight junction protein expression and is closely related to blood-brain barrier permeability [ 36 ]. ERK showed continuous overactivation during brain trauma, and its expression duration was significantly prolonged [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T3 administration after brain ischemia in rodent models stimulates the phosphoinositid-3-kinase/akt pathway (Hiroi et al 2006) and suppresses the mitogen-activated protein kinase (MAPK) pathway (Genovese et al 2013), both of which directly modulate programmed cell death and the inflammatory response. ERK1/2 belongs to the MAPK family and plays a detrimental role in stroke outcome (Schanbacher et al, 2022). ERK is activated by phosphorylation, and this activation was ameliorated by T3 treatment in our stroke model.…”
Section: Discussionmentioning
confidence: 99%
“…As the inhibition of Erk 1/2 is associated with an improved outcome after stroke (C. Schanbacher et al, 2022), the expression and phosphorylation of Erk1/2 were examined in both the cortex and basal ganglia. The expression of Erk1/2 remained constant in all groups following tMCAO (Fig.…”
Section: T3 Administration Reduced Inflammation Thrombosis and Cell D...mentioning
confidence: 99%
“…Moreover, ERK inhibitors U0126 and PD184161 have shown to decrease infarct volume after an ischemic insult [ 24 ]. A recent study has reported that stimulation of ERK1/2 led to an increase in infarct volume, inflammation, and apoptosis after tMCAO [ 44 ], thus indicating that the activation of this pathway is detrimental and that its inhibition is instead neuroprotective. Our results are in close agreement since ischemia-reperfusion significantly increases ERK1/2 phosphorylation/activation in the ischemic hemisphere.…”
Section: Discussionmentioning
confidence: 99%